2011
DOI: 10.1161/circulationaha.110.954404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Systolic Dyssynchrony for Cardiac Resynchronization Therapy Is Clinically Useful

Abstract: T he beneficial effects of cardiac resynchronization therapy (CRT) on morbidity and mortality of heart failure patients with wide QRS complex have been demonstrated extensively. Various single-center and multicenter randomized, clinical trials have shown that CRT improves heart failure symptoms and left ventricular (LV) function and induces a significant reduction in LV volumes and mitral regurgitation. [1][2][3][4] In addition, CRT reduces the number of heart failure hospitalizations and improves long-term su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 84 publications
(120 reference statements)
0
26
0
Order By: Relevance
“…This is a pre-print version The final version can be downloaded from http://www.sciencedirect.com/ between mechanical dyssynchrony and response to CRT is still a controversial issue (Delgado and Bax (2011);Sung and Foster (2011)), particularly limited if a single parameter (measured strain) is considered in the analysis. Comparing the measured strain to the deformation patterns of specific mechanisms involved in CRT response may be a more relevant strategy (Parsai et al (2009)) and this could be achieved with the use of 3D strain analysis by using such a tool as the one we present.…”
mentioning
confidence: 99%
“…This is a pre-print version The final version can be downloaded from http://www.sciencedirect.com/ between mechanical dyssynchrony and response to CRT is still a controversial issue (Delgado and Bax (2011);Sung and Foster (2011)), particularly limited if a single parameter (measured strain) is considered in the analysis. Comparing the measured strain to the deformation patterns of specific mechanisms involved in CRT response may be a more relevant strategy (Parsai et al (2009)) and this could be achieved with the use of 3D strain analysis by using such a tool as the one we present.…”
mentioning
confidence: 99%
“…In recent years, a lot of efforts had been put in the auto-diagnosis of cardiac mechanical dyssynchrony [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, existing methods lack robustness and no existing LV mechanical dyssynchrony measurement methods could predict the response to CRT robustly [15,16]. In this paper, an data-driven approach is proposed to measure the mechanical dyssynchrony of the left ventricle automatically by utilizing effective image and signal processing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Past trials demonstrate that LV mechanical dyssynchrony has superior accuracy compared with LV electric dyssynchrony to predict response to CRT [13,14]. However, a recent trial showed that no single LV mechanical dyssynchrony parameter could predict the response to CRT robustly [15,16]. In [17], the authors pointed out that "although sophisticated cardiac imaging modalities have been intensively utilized for improving patient outcome, it seems that many mechanical dyssynchrony measures suffer from technical limitations and from difficult interpretation of the complex signals, which lack reproducibility outside highly specialized laboratories."…”
Section: Introductionmentioning
confidence: 99%
“…However, of the patients who receive CRT, approximately one-third show no clinical or morphometric response to the therapy [22,23]. This "non-responder" rate has plagued the field, and despite significant efforts, has remained steady.…”
Section: Beyond Left Ventricular Mechanicsmentioning
confidence: 99%